Type 2 fiber predominance in Lambert-Eaton myasthenic syndrome. - Squier, M; Chalk, C; Hilton-Jones, D; Mills, K; Newsom-Davis, J (1991)
Serial muscle biopsies in a noncarcinomatous case of Lambert-Eaton myasthenic syndrome (LEMS) have shown progressive atrophy and loss of type 1 fibers, resulting in overwhelming type 2 predominance. A similar abnormality was found in a single biopsy from a second case of LEMS without associated carcinoma. Review of the literature suggests that type 2 fiber predominance has been observed in at least one other biopsied case. Interference with transmitter release caused by anti-voltage-gated calcium channel antibodies may deprive type 1 muscle fibers of the low frequency discharge necessary to maintain their metabolic properties.